Colecistite aguda por ascaris lumbricoides - Amauri Clemente da Rocha; Severino Lourenço da Silva Júnior; Rodrigo Fernando Lourenço de Amorim (Revista do Colégio Brasileiro de Cirurgiões)
Biliary’s ascariasis is the most often ectopic site of this helminthiasis, but invasion of the worms into the gallbladder is quite rare. The autors report a case of a patient with clinical symptoms, compatible with cholecystitis induced by the worm, as shown by ultrasonography. Treatament was cholecystectomy and antihelmintic drug therapy with a good outcome.